Retroperitoneal mixoide malignant fibrous histiocytoma. - Pérez Billi, Luis; Estefan, Alberto; Kvasina, Tomislav; Beguiristain, Alberto; Nuchowich, Gustavo; Nuchowich, Manuel; Wozniak, Angélica; Glausiuss, José (Cirugía del Uruguay, 1984)
Presenting a case of malignant fibrous histiocytoma, of retroperitoneal topography, its histogenesis, its clinical characteristics and the value of computerized axial tomography in the diagnosis of this condition being pointed out. lt has been found that its anatomopathological typification is essential from the therapeutic and prospectiva point of view.